Emerging biomedical engineering strategies for hair follicle regeneration - Xinyue Cao; Minhui Lu; Ning Li; Lijun Cai; Yu Wang; Yuanjin Zhao (Bioactive Materials)
Hair follicle undergoes cyclical regeneration that relies on the spatiotemporal coordination of epithelial-mesenchymal interactions and multiple signaling pathways. However, hair follicle homeostasis is susceptible to disruption by various endogenous and exogenous factors, leading to hair loss diseases like androgenetic alopecia and scarring alopecia. Traditional pharmacological treatments and surgical transplantation still face challenges in meeting clinical demands because of unstable therapeutic efficacy, limited donor resources, and postoperative complications. In this condition, biomedical engineering has advanced hair follicle regeneration from “replacement therapy” to “functional reconstruction” by integrating interdisciplinary approaches such as stem cell technology, tissue engineering, and modern engineering technology. This review systematically summarizes the latest advancements in biomedical engineering technology in the realm of hair follicle regeneration. We first elucidate hair follicles' structure, cyclic regulatory mechanisms, and main impact factors. Subsequently, we evaluate the advanced in vivo hair follicle regeneration strategies, including cell transplantation, cell reprogramming, biomaterial delivery and other strategies. We then focus on the in vitro hair follicle organoids’ success construction and their applications in hair growth, drug screening, disease modeling and mechanistic studies. Finally, we critically discuss the technical limitations and prospects in this field, providing a theoretical framework for the innovation of future regenerative medicine.